1986
DOI: 10.1152/ajpheart.1986.250.5.h846
|View full text |Cite
|
Sign up to set email alerts
|

Reduced chronotropic responsiveness of the heart in experimental uremia

Abstract: Cardiac beta-adrenoceptor responsiveness was evaluated in experimental uremia by in vivo and in vitro techniques. Uremia was induced in rats by bilateral nephrectomy for 48 h. In rats with chronic intra-arterial and intravenous catheters, cardiovascular reflexes and the renin-angiotensin system were blocked with atropine, pentolinium, and a converting-enzyme inhibitor, respectively. Blood pressure (BP) and heart rate (HR) were continuously recorded. Cumulative doses of isoproterenol were injected intravenously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…On the other hand, there is evidence of diminished β-adrenergic responsiveness [20,30,33], as evidenced by measurements of receptor binding, of postreceptor signaling steps and of the HR response in SNX after stimulation with isoproterenol. α-Adrenoreceptor responsiveness of peripheral vessels is decreased as well [39].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is evidence of diminished β-adrenergic responsiveness [20,30,33], as evidenced by measurements of receptor binding, of postreceptor signaling steps and of the HR response in SNX after stimulation with isoproterenol. α-Adrenoreceptor responsiveness of peripheral vessels is decreased as well [39].…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic tone is consistently raised in patients with ESRD, and CV mortality of these patients is dependent on the level of sympathetic nerve system (SNS) overactivity [4]. Studies in adult uremic rats have revealed that increased SNS activity can either decrease or have no effect on adrenergic receptors [5][6][7]. In the adult, β-adrenergic receptor blockade or the destruction of neuronal inputs to β-adrenergic receptors results in compensatory suprasensitivity of receptor signaling and eventually to upregulation of cell-surface receptors [8].…”
Section: Introductionmentioning
confidence: 99%
“…In chronic uremic rats, the density of · 1 and · 2 receptors in the cerebral cortex was significantly increased, while the ß-adrenergic and muscarinergic receptors in the heart as well as cardiac · 1 adrenoceptors were unchanged [18][19][20]. Studies in uremic rats also show variable decreases in contraction of isolated myocytes along with a decrease in the velocity of shortening and relaxation [21][22][23]. Both energy production and consumption are influenced by uremia [24][25][26].…”
Section: Ckd As the Substrate For Cardiac Arrhythmiasmentioning
confidence: 99%